A dense hydrogen bond-enhanced bio-based supramolecular adhesive and its preparation method and application
By mixing tannic acid with citric acid or glyphic acid, adjusting the density of hydrogen bonds, preparing a biological super molecular adhesive to the enhanced hydrogen bond to solve the problem of insufficient biological adhesive adhesive, and realize the high adhesion strength, and Toughness and reusable effects.
Patent Information
- Application Number
- CN202410391751.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-02
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-04-02
AI Technical Summary
The bonding strength of existing bio-based supramolecular adhesives is weak and difficult to compare with traditional synthetic adhesives.
By mixing tannic acid with citric acid or glyphic acid, the density of non -common price interaction, especially the density of hydrogen bonding, to prepare the biological super molecular adhesives enhanced by hydrogen bonds.
The prepared adhesive shows superior adhesion strength, toughness and resistance to environmental factors. It is suitable for metal adhesion and can be reused.
Smart Images

Figure CN118272042B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesive preparation, and in particular relates to a dense hydrogen bond-reinforced bio-based supramolecular adhesive and a preparation method and application thereof. Background Art
[0002] Sustainability is becoming increasingly critical in the chemical industry and human society due to factors such as dwindling petroleum resources, environmental issues, and the need to develop long-term solutions. One promising direction is to find alternative sources of renewable raw materials, reduce waste and emissions, and adopt environmentally friendly manufacturing processes, which are important steps towards a more sustainable chemical society. The field of adhesive materials has also undergone this evolution, moving from fossil fuel-based to bio-based materials extracted from plant oils, proteins, sugars, and other renewable resources. In ancient times, early humans used natural substances extracted from plants and animals, such as plant resins, tars, and beeswax, to glue objects together. In modern society, the Industrial Revolution brought significant advances in adhesive technology, promoting the development of synthetic adhesives that are multifunctional and high-performance, such as epoxies and acrylics. Although modern adhesives are widely used and effective, they bring environmental impacts and health issues, such as resource depletion, volatile organic compounds (VOCs), toxicity, dependence on non-renewable resources, and long-term degradation.
[0003] Bio-based supramolecular adhesives represent an innovative approach to adhesive technology by combining renewable natural materials with the unique properties of supramolecular interactions. Despite progress, the bonding strength of bio-based supramolecular adhesives is still relatively weak compared to traditional synthetic adhesives due to the inherent weakness of non-covalent interactions. Currently, a large amount of research work is devoted to improving the adhesive properties of adhesives by increasing the adhesion and cohesion strengths. Adhesion refers to the interfacial bonding strength between the adhesive and the adherend, which is generally increased by chemically modifying specific functional groups to increase the interaction strength between the object and the adhesive. Cohesion refers to the mechanical strength of the adhesive itself, which is generally adjusted by changing the non-covalent interaction mode, such as hydrogen bonding, metal coordination bonds, host-guest interactions, etc. It is well known that the cross-linking density of polymers has a great influence on the mechanical strength of materials. Therefore, it is intended to study the effect of the density of non-covalent interactions on the adhesive properties of supramolecular bio-based supramolecular adhesives. By adjusting the density of non-covalent interactions, taking the density of hydrogen bonds as an example, the preparation of bio-based supramolecular adhesives with higher adhesion is achieved. Summary of the invention
[0004] In view of the above problems, the object of the present invention is to provide a dense hydrogen bond-reinforced bio-based supramolecular adhesive and a preparation method and application thereof.
[0005] TA (tannic acid) is a dendritic natural organic compound with multiple phenolic hydroxyl groups. It is widely used in the preparation of bio-based adhesives due to its potential to form multiple non-covalent interactions. MA (malic acid) and CA (citric acid) are a type of natural organic acid with the same chemical structure and different stereostructures. The former is a difunctional linear structure, and the latter is a trifunctional stereostructure. In the process of preparing supramolecular adhesives, under the same feed ratio, the latter forms a higher density of hydrogen bonds. Pure TA cannot form an adhesive, and it crystallizes into a crystalline powder due to the regular arrangement of molecules inside the material.
[0006] When tannic acid and malic acid or citric acid are mixed to prepare a solution, as the solvent water continues to evaporate, the solution will gradually become viscous to form a supramolecular adhesive. This is probably because the single-component tannic acid has a regular structure and is easy to arrange regularly and crystallize, while the mixture of the two components cannot be arranged regularly and has strong hydrogen bonds between molecules, resulting in the formation of an amorphous supramolecular cross-linked polymer.
[0007] The specific technical solutions are as follows:
[0008] A preparation method of a dense hydrogen-bond-enhanced bio-based supramolecular adhesive comprises the following steps: adding water to tannic acid and citric acid or malic acid to prepare a mixed solution, stirring the solution at 40-60°C for 12-24 hours to fully construct a hydrogen-bond network inside the system, and when the reaction degree exceeds its gel point, the solution becomes viscous to obtain a dense hydrogen-bond-enhanced bio-based supramolecular adhesive.
[0009] Furthermore, the amount of tannic acid in the bio-based supramolecular adhesive is 10-40%.
[0010] Furthermore, the amount of tannic acid in the bio-based supramolecular adhesive is 10%.
[0011] Furthermore, after adding water, the concentration of citric acid or malic acid in the solution is 2 mol / L.
[0012] A dense hydrogen-bond-reinforced bio-based supramolecular adhesive prepared by the preparation method.
[0013] Application of a bio-based supramolecular adhesive enhanced by dense hydrogen bonds.
[0014] Beneficial effects of the present invention:
[0015] 1) The adhesive prepared by the present invention exhibits excellent adhesion strength, toughness and resistance to environmental factors;
[0016] 2) The supramolecular adhesive of the present invention is easy to prepare, the raw materials are cheap and readily available, and it is green, environmentally friendly and renewable;
[0017] 3) The adhesive of the present invention can be reused and has bonding effect on different materials, and is particularly suitable for bonding metals. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Schematic diagram of the chemical structure of BSA (CA) in Example 1;
[0019] Figure 2 is a schematic diagram of the chemical structure of BSA (MA) in Example 2;
[0020] Figure 3 The internal hydrogen bond density map of supramolecular adhesive and single-component acid was characterized by NMR;
[0021] Figure 4 The test results of the adhesive properties of supramolecular bio-based adhesives are shown;
[0022] Figure 5 The test results of the adhesion of bio-based adhesive BAS (CA) 0.1 to different materials;
[0023] Figure 6 Solvent resistance and reusability results of bio-based adhesive BAS(CA)0.1. DETAILED DESCRIPTION
[0024] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited thereto.
[0025] Characterization of supramolecular bioadhesives: 1H nuclear magnetic resonance (1H NMR) spectra were obtained at room temperature using a Bruker Advance Ⅲ HD 400 MHz NMR spectrometer (Germany); Fourier transform infrared (FT-IR) spectra were obtained at room temperature using a Perkin-Elmer Paragon 1000 spectrometer, covering a frequency range from 500 cm -1 to 4000 cm -1 , Powder X-ray diffraction (PXRD) was performed at room temperature using an XRD instrument (Ultima IV, Rigaku, Japan) in the 2θ range of 5–80°.
[0026] Thermal behavior tests: Differential scanning calorimetry (DSC) was performed in a nitrogen atmosphere with a heating range of 35–800 °C and a heating rate of 10 °C / min (SDT-Q600, TA Instrument, USA); thermogravimetric analysis (TGA) was performed in a steady nitrogen flow with a heating rate of 5 °C / min in the temperature range of 30–800 °C.
[0027] Tensile shear adhesion test: An appropriate amount of bio-based adhesive was applied to the substrate (area: 10 mm × 20 mm), a tensile shear joint was formed by hot pressing, and then left to cool to room temperature. Subsequently, the bonding performance was tested using a universal tensile testing machine; the shear adhesion strength was calculated by dividing the maximum force at the joint failure by the overlapping contact area. Each set of sample data was tested at least 3 times and the average value was calculated.
[0028] Example 1
[0029] Preparation of supramolecular bioadhesive
[0030] TA and CA were added to a 50 mL flask, and then deionized water was added. After adding water, the concentration of CA in the solution was 2 mol / L. The mixture was stirred at 60 °C for 12 hours until the solution became viscous (the flask was open). The adhesive BSA (CA) 0.1 was obtained. The amount of tannic acid in the bio-based supramolecular adhesive was 10%, and then it was directly used for bonding and other tests without further purification and separation. Its chemical structure is as follows Figure 1 As shown, a denser hydrogen bond network is formed inside the bio-based adhesive BAS (CA).
[0031] Example 2
[0032] Preparation of supramolecular bioadhesive
[0033] TA and MA were added to a 50 mL flask, and then deionized water was added. After adding water, the concentration of MA in the solution was 2 mol / L. The mixture was stirred at 60 °C for 12 hours until the solution became viscous (the flask was open). The adhesive BSA (MA) 0.1 was obtained. The molar concentration of tannic acid in the bio-based supramolecular adhesive was 10%, and then it was directly used for bonding and other tests without further purification and separation treatment. Its chemical structure is shown in Figure 2 As shown in Figure 3, a relatively loose hydrogen bond network is formed inside the bio-based adhesive BAS (MA).
[0034] The adhesives of Examples 1-2 and the single-component citric acid, tannic acid and malic acid were characterized by H NMR spectra. Figure 3 As shown, H A represents the hydrogen on the adjacent carbon of the hydroxyl group of tannic acid, H B is the hydrogen on the adjacent methylene of the carboxyl group of the malic acid molecule, H C and H DRepresent the hydrogens of the carboxyl and hydroxyl groups of malic acid, respectively. From the H NMR spectrum, we can see that the H NMR peaks of the formed adhesives are not generated relative to the building blocks, indicating that no chemical reaction occurred during this process, but non-covalent interactions occurred. In addition, it can be clearly seen that the H A The peaks of the two groups shifted to lower displacement, and the former shifted more significantly, which indicated that a large number of hydrogen bonds were formed in the adhesive BSA, while the hydrogen bond density in BSA(CA) was larger and the shielding effect was stronger, making H A The peak shifts to higher fields more obviously.
[0035] Embodiment 3-5
[0036] Preparation of supramolecular bioadhesive
[0037] The amount of tannic acid in the bio-based supramolecular adhesive was changed to 20%, 30% and 40% respectively, and the other operating conditions were the same as those in Example 1, to obtain adhesives BSA(CA)0.2, BSA(CA)0.3 and BSA(CA)0.4.
[0038] Embodiment 6-8
[0039] The amount of tannic acid in the bio-based supramolecular adhesive was changed to 20%, 30% and 40% respectively, and the other operating conditions were the same as those in Example 2, to obtain adhesives BSA(MA)0.2, BSA(MA)0.3 and BSA(MA)0.4.
[0040] Example 9
[0041] The adhesives BSA(MA)x and BSA(CA)x of Examples 1-8 and single-component citric acid and malic acid were tested for their adhesion to stainless steel plates, where the number x represents the molar ratio of TA in the adhesives BSA(MA) and BSA(CA). Figure 4It can be found that (where (a) represents the relationship between the adhesive displacement and lap shear strength of BSA(MA)x, (b) represents the adhesive strength of BSA(MA)x, obtained from (a), (c) represents the relationship between the adhesive displacement and lap shear strength of BSA(CA)x, and (d) represents the adhesive strength of BSA(CA)x, obtained from (c)) pure MA has certain adhesive properties, but the adhesive strength is relatively poor, which is 1.0MPa. As x increases (the amount of tannic acid in the bio-based supramolecular adhesive increases), from 0 to 0.4, its adhesive properties first increase and then decrease, and the strongest BAS(MA) corresponding to 0.1 is 4.0 MPa, which is probably because with the increase of TA content, the relatively rigid structure of TA and the increase of hydrogen bond crosslinking density make the cohesion of adhesive BAS(MA) stronger, and the bonding performance also becomes stronger; when the TA component in BAS(MA) exceeds a certain critical value, the TA component is dominant, the crystallinity of the adhesive gradually becomes stronger, the adhesion strength becomes weaker, and the bonding performance also weakens. At the same ratio, BAS(CA) has stronger bonding performance than BAS(MA), and the strongest is 6.0 MPa corresponding to BAS(CA)0.1. The experimental results fully show that the increase of hydrogen bond density inside the supramolecular adhesive will enhance the bonding performance of the adhesive to a certain extent.
[0042] Example 10
[0043] Test BAS(CA)0.1 for lap shear strength of different materials, such as Figure 5As shown in ((a) represents the relationship between the adhesive displacement and lap shear strength of BAS(CA)0.1 for different materials, (b) represents the adhesive strength of BAS(CA)0.1 for different materials, obtained from (a), (c) represents the relationship between the adhesive displacement and lap shear strength of BAS(CA)0.1 when different materials are bonded to each other, (d) represents the adhesive strength of BAS(CA)0.1 when different materials are bonded to each other, obtained from (c)), the experimental results show that BAS(CA)0.1 has good bonding performance to metal materials, among which the bonding strength to stainless steel (SS), iron (Fe) and aluminum (Al) are 6.0 MPa, 3.2 MPa and 2.4 MPa respectively; however, for samples of plastic polymer materials, BAS(CA)0.1 exhibits poor bonding performance, among which the bonding strength to polycarbonate (PC) and polypropylene (PP) plastics is only 0.6 MPa and 0.4 MPa, The bonding performance of BAS(CA)0.1 to two samples of different materials was tested. The results showed that the bonding performance of stainless steel with iron, aluminum, polycarbonate plastic and polypropylene plastic gradually decreased, and their bonding strengths were 6.0 MPa, 4.7 MPa, 4.1 MPa, 1.2 MPa and 0.6 MPa, respectively. The changing trend of the experimental results was consistent with the above experiment, because the adhesive BAS(CA)0.1 remained unchanged during the entire experiment, that is, the cohesive force remained unchanged, and the deterioration of the bonding performance was probably due to the difference in the adhesion strength of BAS(CA)0.1 to different materials. BAS(CA)0.1 destroyed the cohesive force of stainless steel, partially destroyed the interfacial adhesion of iron, aluminum and polycarbonate plastic, and completely destroyed the interfacial adhesion of polypropylene plastic. Therefore, BAS(CA)0.1 is more suitable for bonding samples made of metal materials, and the study of the bonding mechanism also laid the foundation for the design of universal bio-based supramolecular adhesives.
[0044] Embodiment 11
[0045] An adhesive with excellent performance and environmental friendliness should have good bonding performance and reusability in different environments, such as Figure 6As shown in the figure ((a) represents the relationship between the adhesive displacement and lap shear strength of BAS(CA)0.1 under different solvent conditions, (b) represents the adhesive strength of BAS(CA)0.1 under different solvent conditions, obtained from (a), (c) represents the relationship between the adhesive displacement and lap shear strength of BAS(CA)0.1 under repeated use, (d) represents the adhesive strength of BAS(CA)0.1 under repeated use, obtained from (c)), the solvent resistance and reusability of BAS(CA)0.1 to organic reagents of different polarities PE, DCM, THF, EA, and MeCN were tested, and the bonding performance of the stainless steel sheets bonded by BAS(CA)0.1 was tested after being immersed in the solvent for 24 hours. The results showed that with the increase of the polarity of the organic solvent used, the adhesion of BAS(CA)0.1 to the stainless steel sheets gradually weakened, among which the strongest was 6.0 MPa in the absence of solvent, and after being immersed in PE, DCM, THF, EA, and MeCN, the bonding strength decreased to 3.3 MPa, 2.3 MPa, 1.8 MPa, 1.1 MPa and 0.9 MPa, which is probably because the high polarity solvent destroyed the hydrogen bonds inside the supramolecular adhesive BAS(CA)0.1, thereby reducing the strength of adhesion and gradually weakening the bonding performance. In addition, the results of repeated experiments show that BAS(CA)0.1 can be recycled and can be turned back into a viscous state after heating. After being reused ten times, the bonding strength is still about 5.0 MPa, and the strength decreases by only 17%. The above experimental results show that BAS(CA)0.1 has good resistance to low polarity organic solvents and repeated use.
Claims
1. A method for preparing a dense hydrogen-bond-enhanced bio-based supramolecular adhesive, characterized in that: The method comprises the following steps: adding water to tannic acid and citric acid or malic acid to mix to prepare a mixed solution, stirring at 40-60°C for 12-24 hours, constructing a hydrogen bond network inside the system, and when the reaction degree exceeds its gel point, the solution becomes viscous to obtain a dense hydrogen bond-enhanced bio-based supramolecular adhesive.
2. The preparation method according to claim 1, characterized in that The amount of tannic acid in bio-based supramolecular adhesives is 10-40%.
3. The preparation method according to claim 1, characterized in that: The amount of tannic acid in the bio-based supramolecular adhesive is 10%.
4. The preparation method according to claim 1, characterized in that: After adding water, the concentration of citric acid or malic acid in the solution is 2 mol / L.
5. A dense hydrogen-bond-reinforced bio-based supramolecular adhesive prepared by the preparation method according to any one of claims 1 to 4.
6. An application of the dense hydrogen bond enhanced bio-based supramolecular adhesive as claimed in claim 5, characterized in that: Used for bonding metal materials.
Citation Information
Cited By
Full-bio-based high-performance flame-retardant adhesive based on epoxidized soybean oil / citric acid / tannic acid / nano-hydroxyapatite and preparation method of full-bio-based high-performance flame-retardant adhesive
CN120865838A